A feedback system that combines monitoring of systolic blood pressure and relative blood volume in order to prevent hypotensive episodes during dialysis. (September 2019) - Atallah, Richard; Bauer, Florian; Strohhöfer, Christof; Haueisen, Jens
Highlights: Monitoring one single physiological parameter during hemodialysis does not give high insights on cadiovascular stability. Monitoring two physiological variables provides a better assessment of the cardiovascular status of the patient. Combining blood pressure and relative blood volume to decreases significantly the occurrence of hypotensive episodes. Abstract: Hypotensive Episodes (HEs) are one of the most common complications during dialysis. Occurrence of HEs can be reduced by applying physiological closed loop systems that monitor physiological parameter(s) and adjust dialysis related parameter(s). We developed a physiological closed loop control system (PCLCS) that monitors systolic blood pressure (sysBP) and relative blood volume (RBV) and calculates the net fluid removal (nfr) rate during dialysis. The performance of PCLCS was compared in the laboratory to a feedback system that monitors only RBV (BVFS). A laboratory test setup was developed to test the feedback systems. The test setup simulates nfr-rate and refilling of a patient's intravascular fluid. We studied the impact of the feedback systems PCLCS and BVFS on the number of HEs ( sysBP < 90 mmHg), on the variance of sysBP and RBV, on pre to post sysBP and RBV and on the achievement of the nfr-volume. PCLCS allowed 80% less HEs than BVFS ( p < 0.001). Variance of sysBP and RBV were reduced by 41.8% and by 52% ( p < 0.001), respectively, when using PCLCS. There were no differences between pre to post sysBP nor between pre to post RBV when comparing PCLCS to BVFS. The nfr-volume was achieved by both feedback systems.